Health supervision for people with Bloom syndrome. Issue 9 (28th July 2018) - Cunniff, Christopher; Djavid, Amir Reza; Carrubba, Steven; Cohen, Bernard; Ellis, Nathan A.; Levy, Carolyn Fein; Jeong, Stacy; Lederman, Howard M.; Vogiatzi, Maria; Walsh, Michael F.; Zauber, Ann Graham
Abstract : Bloom Syndrome (BSyn) is an autosomal recessive disorder that causes growth deficiency, endocrine abnormalities, photosensitive skin rash, immune abnormalities, and predisposition to early‐onset cancer. The available treatments for BSyn are symptomatic, and early identification of complications has the potential to improve outcomes. To accomplish this, standardized recommendations for health supervision are needed for early diagnosis and treatment. The purpose of this report is to use information from the BSyn Registry, published literature, and expertise from clinicians and researchers with experience in BSyn to develop recommendations for diagnosis, screening, and treatment of the clinical manifestations in people with BSyn. These health supervision recommendations can be incorporated into the routine clinical care of people with BSyn and can be revised as more knowledge is gained regarding their clinical utility.